2011
DOI: 10.4061/2011/932351
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Multiple Sclerosis: Scratching the Surface of a Complex Disease

Abstract: Multiple Sclerosis (MS) is the most common demyelinating disease of the central nervous system. Although the etiology and the pathogenesis of MS has been extensively investigated, no single pathway, reliable biomarker, diagnostic test, or specific treatment have yet been identified for all MS patients. One of the reasons behind this failure is likely to be the wide heterogeneity observed within the MS population. The clinical course of MS is highly variable and includes several subcategories and variants. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 119 publications
0
73
0
2
Order By: Relevance
“…These results indicated that [ 11 C] DAC-PET could be used to noninvasively diagnose neuroinflammation and to monitor therapeutic effectiveness in EAE. The diagnostic criteria of MS have evolved from being solely clinical symptom-based to integrating evoked potentials, spinal fluid analysis and magnetic resonance imaging assessments (Fox and Cohen 2001;Kalkers et al 2002); however, MS is still very difficult to diagnose and evaluate because of its profound heterogeneity in pathomorphology, clinical course and therapeutic response (McFarland and Martin 2007;Disanto et al 2010). Abundant evidence strongly supports that neuroinflammation lesions occur early during the disease course and that they are prominent from the onset of MS (McFarland and Martin 2007;Glass et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that [ 11 C] DAC-PET could be used to noninvasively diagnose neuroinflammation and to monitor therapeutic effectiveness in EAE. The diagnostic criteria of MS have evolved from being solely clinical symptom-based to integrating evoked potentials, spinal fluid analysis and magnetic resonance imaging assessments (Fox and Cohen 2001;Kalkers et al 2002); however, MS is still very difficult to diagnose and evaluate because of its profound heterogeneity in pathomorphology, clinical course and therapeutic response (McFarland and Martin 2007;Disanto et al 2010). Abundant evidence strongly supports that neuroinflammation lesions occur early during the disease course and that they are prominent from the onset of MS (McFarland and Martin 2007;Glass et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The lesions at early phase are characterized by the presence of infiltrated inflammatory cells around venules and small veins. MS remains difficult to diagnose because of its profound heterogeneity in pathomorphology, clinical course and therapeutic response (Martin et al 2001;Disanto et al 2010). Trials have shown that an early diagnosis can make a marked difference to the efficacy of MS drug treatments (Hartung 2005;Heesen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of multiple sclerosis (MS) involves inflammatory demyelination, thought to involve the activation of autoreactive T cells that in turn activate microglia and recruit macrophages, which cause demyelination and subsequent neurological damage (Disanto et al, 2010;Nylander and Hafler, 2012). In addition, meningeal ectopic B cell follicles and plasmablasts in the CSF have been reported; these cells are also likely to contribute to the pathology of MS (Aloisi et al, 2010;Meinl et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…10 In SPMS, relapses are not followed by periods of full neurological recovery and deficits accumulate as the MS progresses. 11 The accumulated deficits must persist for 6 or more months to meet the criteria for SPMS. 12 The remaining estimated 15% of CDMS patients experience a primary progressive clinical course.…”
Section: Introductionmentioning
confidence: 99%